Mapping the trajectory of the stria terminalis of the human limbic system using high spatial resolution diffusion tensor tractography. (3rd November 2015) - Kamali, Arash; Yousem, David M.; Lin, Doris D.; Sair, Haris I.; Jasti, Siva P.; Keser, Zafer; Riascos, Roy F.; Hasan, Khader M.
Highlights: We present for the first time, detailed DTI based anatomic description of the stria terminalis connections. Revealing the forniceal columns including the precommissural and postcommissural fibers. Reviewing the advantages of our high resolution diffusion tensor tractography protocol. Abstract: The human limbic system is composed of gray and white matter structures which have been known to have a role in core processes such as motivation, memory, emotion, social behavior, self-awareness as well as certain primitive instincts. Multiple functional studies investigated some of these brain tasks in human brain limbic system. However, the underlying fine fiber pathways of the limbic system including the trajectory of the stria terminalis have not been delineated separately by prior diffusion weighted imaging. The ability to trace the underlying fiber anatomy noninvasively using diffusion tensor tractography (DTT) would be helpful to study the neurophysiology of these tracts in different functions in future functional studies. Few studies have focused on the stria terminalis using diffusion tensor tractography. Yet, the trajectory of the stria terminalis and some fine subtrajectories of the fornix have not been elucidated by prior DTT studies. We decided to further investigate these fine neuronal trajectory using tractography and high spatial resolution diffusion tensor imaging on 3T. Fifteen healthy right-handed men (age range 24–37 years) were studied. We delineated the detailed trajectories of the stria terminalis and fornix bilaterally in fifteen normal adult human brains. Using a high resolution DTT technique, we demonstrate for the first time, the trajectory of stria terminalis as well as detailed precommissural and postcommissural connectivity of the forniceal columns.